Intranasal Dexmedetomidine Accompanied by Cartoon Video Preoperation for Reducing Emergence Delirium in Children Undergoing Strabismus Surgery: A Prospective Randomized Trial - Chu, Liyan; Wang, Yue; Wang, Shanshan; Su, Shaofei; Guo, Zhixing; Wang, Guyan (Frontiers in Surgery, 2021)
Background: After general anethesia, many pediatric patients present with emergence delirium (ED). The aim of this study was to determine whether dexmedetomidine intranasal premedication accompanied by a cartoon video 30 minutes before general anesthesia would have an effect on reducing emergence delirium in preschool children. Methods: One hundred and forty children aged 3-6 yr undergoing elective strabismus surgery were randomly to be premedicated with 2 µg kg-1 intranasal dexmedetomidine accompanied by the viewing of a cartoon video (Group DV) or without any premedication as usual (Group C). The primary outcome was the incidence of emergence delirium at the postanesthesia care unit (PACU), evaluated by the Pediatric Anesthesia Emergence Delirium (PAED) scale. The secondary outcomes included: the Modified Yale Preoperative Anxiety Scale (mYPAS) upon separation from parents; the Induction Compliance Checklist score (ICC); the PACU discharge time; the parental satisfaction score; the incidences of the side effects and the Post-Hospital Behavior Questionnaire (PHBQ) score during the first day after surgery. Results: The incidence of emergence agitation (PAED score≥10) was reduced in Group DV compared with Group C [8 of 70 (11.4%) vs 24 of 70 (34.3%); P=0.001]. None of the patients in the DV group experienced severe emergence agitation (PAED score≥15), as compared with the C group (P=0.006). The mYPAS score upon separation from parents (P<0.001) and the incidence of poor coordination (ICC ≥4) during induction (P<0.001) were significantly lower in Group DV than in Group C. In Group DV, the PACU discharge time was longer (P<0.001), and the parental satisfaction score was higher (P<0.001). However during the first day after surgery, the PHBQ score was lower in Group DV compared with Group C (P=0.001). Conclusions: Premedication with 2 µg kg-1 intranasal dexmedetomidine accompanied by cartoon video viewing can dramatically reduce emergence delirium in preschool children undergoing strabismus surgery, relieve preoperative anxiety and improve the parental satisfaction and the postoperative behavior changes during the first day after surgery.